2015
DOI: 10.22256/pubvet.v8n6.1687
|View full text |Cite
|
Sign up to set email alerts
|

Algumas considerações sobre o sistema radicular de plantas forrageiras

Abstract: ResumoAo descrever e estudar organismos vegetais, é normal subdividi-los em partes acima da superfície do solo, denominada parte aérea e a parte abaixo da superfície do solo, denominada parte subterrânea. Na maioria das pesquisas com pastagens, o estudo do crescimento e do desenvolvimento da parte aérea das plantas é priorizado em detrimento à sua interdependência com as raízes e à influência dos atributos físicos e químicos do solo, do clima e do manejo da planta forrageira sobre essas variáveis. Portanto, um… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 17 publications
1
3
0
Order By: Relevance
“…The nitrogen content of litter was lower (P < 0.05) for pastures fertilized with an N level of 400 kg (Table 7), with no interaction between fertilization and supplementation for this nutrient. The results are coherent, considering the mobility of N in the plant (SILVA et al, 2014). The smaller portion of nitrogen compounds in the degrading material probably resulted from remobilization to the younger parts of the plant.…”
Section: Littersupporting
confidence: 51%
See 1 more Smart Citation
“…The nitrogen content of litter was lower (P < 0.05) for pastures fertilized with an N level of 400 kg (Table 7), with no interaction between fertilization and supplementation for this nutrient. The results are coherent, considering the mobility of N in the plant (SILVA et al, 2014). The smaller portion of nitrogen compounds in the degrading material probably resulted from remobilization to the younger parts of the plant.…”
Section: Littersupporting
confidence: 51%
“…Root growth can be stimulated at a dose of 400 kg N, which may have contributed to the accumulation of P in dead tissues. In a review, Silva et al (2014) found that the greatest root growth of P. guenoarum occurred at a dose of 400 kg.ha -1 .…”
Section: Resultsmentioning
confidence: 99%
“…Silva et al (2009) evaluated seven cultivars of Panicum maximum (including Massai, Mombasa and Tanzania) and observed that flooding significantly reduced total forage production. Silva et al (2014) explain that the production capacity of the shoots of a plant is a result of the action of its root system, as both interact. Root growth under physically limited conditions significantly reduces the total weights of the plants, suggesting that this growth is related to the functional capacity of the root system and also the balance between the root system and shoots will always be reestablished.…”
Section: Shoot Dry Mass Of the Panicum Maximum Grassmentioning
confidence: 99%
“…The higher values of root mass and volume result in greater exploration in the soil profile, which leads to greater utilization of nutrients and capacity to reach deeper water reserves (Silva et al, 2020). The growth of forage species is represented not only by the aerial part, but also by its root development, since the root is the path for the entry of water and nutrients (Silva et al, 2014;Silva et al, 2020). When comparing the two extreme conditions to which the plants were subjected, it can be noted that in the flooded soil, the cultivar BRS Zuri produced the higher root dry mass and root volume compared to plants that received the lowest water availability.…”
Section: Root Dry Mass and Volume Of The Panicum Maximum Grassmentioning
confidence: 99%